Clinical Assessment and Diagnosis of Germline Predisposition to Hematopoietic Malignancies: The University of Chicago Experience - Desai, Ami V.; Perpich, Melody; Godley, Lucy A. (Frontiers in Pediatrics, 2017)
With the increasing use of clinical genomics to guide cancer treatment and management, there is a rise in the identification of germline cancer predisposition syndromes and a critical need for patients with germline findings to be referred for surveillance and care. The University of Chicago Hematopoietic Malignancies Cancer Risk Team has established a unique approach to patient care for individuals with hereditary hematologic malignancies through close communication and coordination between our pediatric and adult programs. Dedicated program members, including physicians, nurses, genetic counselors, and clinical research assistants, screen individuals for cancer predisposition at initial diagnosis through survivorship, in addition to testing individuals with an established family history of a cancer predisposition syndrome. Sample procurement, such as a skin biopsy at the time of bone marrow aspirate/biopsy in individuals with a positive screen, has facilitated timely identification of clinical germline findings or has served as a pipeline for translational research. Our integrated translational research program has led to the identification of novel syndromes in collaboration with other investigators, which have been incorporated iteratively into our clinical pipeline. Individuals are referred for clinical assessment based on personal and family history, identification of variants in susceptibility genes via molecular tumor testing, and during evaluation for matched related allogeneic stem cell transplantation. Upon referral, genetic counseling incorporates education with mindfulness of the psychosocial issues surrounding germline testing at different ages. The training and role of genetic counselors continues to grow, with the discovery of new predisposition syndromes, in the age of improved molecular diagnostics and new models for service delivery, such as telemedicine. With the identification of new syndromes that may predispose individuals to hematologic malignancies, surveillance guidelines will continue to evolve and may differ between children and adults. Thus, utilizing a collaborative approach between the pediatric and adult oncology programs facilitates care within families and optimizes the diagnosis and care of individuals with cancer predisposition syndromes.